2,6-anhydro-1-deoxy-3,4-O-isopropylidene-3-C-methyl-beta-D-ribo-hex-2-ulo-furanose - Curran, L; Jenkinson, S; Jones, N; Watkin, D; Fleet, G (2007)
The relative configuration of the title compound, C10H16O4, was firmly established by X-ray crystallographic analysis. The absolute configuration was determined by the use of 2-C-methyl-d-ribono-1,4-lactone as the starting material. © International Union of Crystallography 2007.